Estudo da (in)existência de sinais em libras a partir da semântica focada na agricultura familiar e proposta de glossário - MAGALHÃES, Claudia do Socorro Azevedo (2021)
This dissertation is inserted in the studies of the (in)existence of signs in the Brazilian Sign Language- BSL/Libras based on the semantics focused on Family Farming and has as its basic principle the terminological, lexicographic studies and the linguistic structure of the Brazilian Sign Language- BSL/Libras. The research is justified by the lack of existence of registration and documentation of terms/signs of the Agrarian and Environment Areas in the BSL, a factor that interferes in the meaning of concepts used in the interaction between teachers, students, translators/interpreters and professionals involved with the inclusion generally. The objective of this study was to research the existence of specific terms of Family Farming in the BSL, to propose neologisms for nonexistent terms and to organize a bilingual glossary with new signs, as well as the signs already are used in the linguistic system of visuospatial languages. The research is classified as descriptive and interpretive with a quantitative and qualitative approach in the first stage and received support from a focus group in the second stage. The methodological path used was based on selecting terms and concepts in Portuguese, from specific dictionaries of the Agrarian and Environmental Areas. The unknown terms of the researcher, unknown to the first forty-nine research subjects and not found in the BSL dictionaries, were structured for conceptual analysis. To validate the concepts of the terms in Portuguese, the focus group was chosen with the participation of ten teachers from the Agrarian and Environmental Areas. The process of creating the terms/signs was proposed on video by a group of nineteen BSL teachers and interpreters from various Educational Institutions in the Amazon and presented to the local Deaf Association. As a result, we obtained fifty terms from the sixty-four initially selected, which had their signs created and/or cataloged in a bilingual glossary. Thus, we present the bilingual glossary entitled “Terms of Family Farming in Libras” as a relevant tool for accessing communication between professionals in the areas and whoever may be interested.